The influence of polyethyleneimine dosages and molecular weight on sedimentation and rheology behavior of copper tailings. Issue 9 (15th July 2020) - Zhang, Wei; Sun, Chunbao; Kou, Jue; Xing, Yi; Gong, Daozhen; Li, Shuofu; Su, Min
Abstract: Polyethyleneimine (PEI) is a kind of modifier and flocculant with good adsorption to heavy metal ions, but there is a lack of literature investigate the influence of polyethyleneimine (PEI) dosages and molecular weight on sedimentation and rheology behavior of copper tailing suspension. In this research, the influence of PEI dosages and molecular weight on sedimentation and rheology behavior were characterized which is supported by measurements and calculation of initial sedimentation rate, turbidity, zeta potential, the contents of heavy metal ions in the supernatant, FT-IR analysis, shear stress and yield stress. With the application of lower molecular weight PEI or PEI_1800, the lower yield stress and inter-aggregate bridging force are obtained, the re-conformation rate is higher than the non-equilibrium flocculation rate between copper tailing particles which results in more charged PEI segments propagating into the suspension. The calculation of interaction energy shows that the smaller floc size is obtained when PEI_1800 or lower molecular weight PEI is used, which is also confirmed by the sedimentation behavior and rheology behavior. In 29 wt% copper tailing suspensions at pH∼9, PEI has a better adsorption performance on Cu 2+ and Pb 2+ . The correlations between PEI molecular weight, polyethyleneimine dosages, yield stress, sedimentation behavior, interaction energy and mechanisms are analyzed of copper tailing suspensions with PEI. Graphical Abstract: